2019
DOI: 10.3892/ijo.2019.4779
|View full text |Cite
|
Sign up to set email alerts
|

Phospho‑STAT1 expression as a potential biomarker for anti‑PD‑1/anti‑PD‑L1 immunotherapy for breast cancer

Abstract: In the present study, we evaluated the mechanisms of programmed death ligand 1 (PD-L1) expression in the breast cancer microenvironment, focusing on the role of interferon-γ (IFN-γ), and the clinical indications for anti-programmed cell death 1 (PD-1) /anti-PD-L1 immunotherapy. We evaluated PD-L1 expression in 4 breast cancer cell lines in the presence of 3 types of inhibitors, as well as IFN-γ. The expression of phosphorylated signal transducer and activator of transcription 1 (p-STAT1), one of the IFN-γ sign… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
44
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 44 publications
(51 citation statements)
references
References 38 publications
(46 reference statements)
4
44
0
Order By: Relevance
“…Recently, several studies have shown that various transcriptional factors, such as STAT1 [44], STAT3 [45], BRD4 [23], NF-kB [18], PI3K/AKT/mTOR [46], and MEK1/2/ERK1/2 [47], promoted PD-L1 transcription in cancer cells. By carrying out a drug sensitivity assay and several verification experiments, we determined that ITGA2 bound with STAT3 to initiate the transcription of PD-L1 by increasing the phosphorylation level of STAT3 in cancer cells.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, several studies have shown that various transcriptional factors, such as STAT1 [44], STAT3 [45], BRD4 [23], NF-kB [18], PI3K/AKT/mTOR [46], and MEK1/2/ERK1/2 [47], promoted PD-L1 transcription in cancer cells. By carrying out a drug sensitivity assay and several verification experiments, we determined that ITGA2 bound with STAT3 to initiate the transcription of PD-L1 by increasing the phosphorylation level of STAT3 in cancer cells.…”
Section: Discussionmentioning
confidence: 99%
“…The CD8 T effector gene signature was previously established to identify activated T cells such as cytotoxic T lymphocytes (20). The signature scores were calculated by averaging the expression levels of the genes included in each signature (22), excluding HLA-DRA expression values, as these were not available in TCGA RNA-seq data.…”
Section: Methodsmentioning
confidence: 99%
“…Later, Weichselbaum and coworkers could show a predictive impact of an IFN-related gene signature with regard to the response to chemotherapy and the efficiency of radiation in breast cancer [ 14 ]. In addition, IFN-γ-related gene signatures predicted clinical response to programmed cell death protein 1 (PD-1)/programmed cell death 1 ligand 1 (PD-L1)-inhibiting therapeutic agents in breast cancer [ 15 ] and in other malignancies [ 16 ]. However, studies on the prognostic role of IFN-γ yielded contradictory results [ 17 ].…”
Section: Introductionmentioning
confidence: 99%